The Impact of Job Stress and Job Satisfaction on Workforce Productivity in an Iranian Petrochemical Industry - Naser Hoboubi; Alireza Choobineh; Fatemeh Kamari Ghanavati; Sareh Keshavarzi; Ali Akbar Hosseini (Elsevier, 2017)
Background: Job stress and job satisfaction are important factors affecting workforce productivity. This study was carried out to investigate the job stress, job satisfaction, and workforce productivity levels, to examine the effects of job stress and job satisfaction on workforce productivity, and to identify factors associated with productivity decrement among employees of an Iranian petrochemical industry. Methods: In this study, 125 randomly selected employees of an Iranian petrochemical company participated. The data were collected using the demographic questionnaire, Osipow occupational stress questionnaire to investigate the level of job stress, Job Descriptive Index to examine job satisfaction, and Hersey and Goldsmith questionnaire to investigate productivity in the study population. Results: The levels of employees' perceived job stress and job satisfaction were moderate-high and moderate, respectively. Also, their productivity was evaluated as moderate. Although the relationship between job stress and productivity indices was not statistically significant, the positive correlation between job satisfaction and productivity indices was statistically significant. The regression modeling demonstrated that productivity was significantly associated with shift schedule, the second and the third dimensions of job stress (role insufficiency and role ambiguity), and the second dimension of job satisfaction (supervision). Conclusion: Corrective measures are necessary to improve the shift work system. "Role insufficiency" and "role ambiguity" should be improved and supervisor support must be increased to reduce job stress and increase job satisfaction and productivity.